Cultural Tourism Development Strategy at The Siak Palace, Siak Sri Indrapura Regency - Ibrahim, Mariaty; Augustin, Jeneva; Fadli, Mashur (CV. Inara, 2025)
Riau is a province rich in history. Many historical heritage buildings can be found in Riau, one of which is the Siak Sri Indrapura Palace. This palace is a historical legacy of the Siak Sultanate, once inhabited by the Sultan of Siak, and today serves as one of the tourism attractions in Siak Regency. The proper development of the tourism sector has the potential to attract both domestic and international tourists to visit and spend money during their travels. In this context, particularly concerning the development of the Siak Palace as a tourist attraction, internal and external environmental analyses are conducted to identify strengths, weaknesses, opportunities, and threats through a SWOT analysis. Furthermore, this study also examines the long-term goals of the Tourism Office, particularly in achieving its mission over the next five years. The research evaluates whether the strategies implemented have been successful by reviewing the annual targets set by the Siak Regency Tourism Office and the policies employed to achieve them. These policies consist of guidelines, rules, and procedures established to support the intended objectives. The findings indicate that the Tourism Office of Siak Regency has carried out the strategic planning process effectively. Every aspect of strategic planning has been implemented optimally and in accordance with the established regulations. However, despite the successful implementation of the strategic plan, the process has not yet fully maximized the development of the Siak Palace as a tourism destination, as further actions beyond the current plans are still required. Tourism development in Siak Sri Indrapura is pursued through the development of tourism resources and the creative economy, enhancement of tourist attractions, and tourism marketing. Nevertheless, these efforts have not yet been fully optimized and therefore need improvement in order to better manage and advance tourism development in Siak Regency. The factors influencing tourism development strategies include budget, human resources, and community participation. Successful tourism development requires cooperation to achieve the desired outcomes, while the government is also expected to pay greater attention to the condition of tourism objects.